Methods for improved flexural mechanical properties of 3D-plotted PCL-based scaffolds for heart valve tissue engineering - Ragaert, Kim (Strojniški vestnik, 2013)
While porous PCL scaffolds can be manufactured trough 3D plotting with high regularity and reproducibility, it has been a challenge in previous research to mimick the highly flexible behaviour of the natural valve leaflets. In this study, an exploration is made of two separate approaches for the improved flexibility of 3D plotted poly--caprolactone (PCL) scaffolds for heart valve leaflets. Firstly, the scaffold geometry is radically altered towards a very open woven-like structure, by adequately adapting the processing parameters during 3D plotting. Secondly, the base material itself is altered by blending a fraction of low-molecular weight poly-ethylene-oxide (PEO) in the PCL polymer. Scaffolds are 3D plotted for both series and their flexibility is evaluated in an uni-axial indentation experiment. The results are compared to those of the natural valve tissue and it is found that both methodologies result in the desired reduction of the stiffness of the scaffold.
Keywords: 3D plotting; 3D-tiskanje; flexure; heart valves; mechanical properties; mehanske lastnosti; ogrodje; scaffolds; srčne zaklopke; tissue engineering; tkivni inženiring; upogibanje